The burden of liver cirrhosis in mortality: Results from the global burden of disease study - Ye, Fei; Zhai, Mimi; Long, Jianhai; Gong, Yi; Ren, Chutong; Zhang, Dan; Lin, Xiang; Liu, Sushun (Frontiers in Public Health, 2022)
Background Liver cirrhosis-related death is a serious threat worldwide. The number of studies exploring the mortality trend of cirrhosis caused by specific etiologies was limited. This study aimed to demonstrate the pattern and trend based on the data of global burden of disease (GBD). Methods The data of cirrhosis mortality were collected from the GBD 2017. The Age standardized mortality rate (ASR) and estimated annual percentage changes (EAPC) were used to estimate the temporal trend of liver cirrhosis mortality by etiologies, regions, sociodemographic index (SDI), and sexes. Results Globally, mortality cases of cirrhosis increased by 47.15%. Although the global ASR of cirrhosis mortality remained stable during this period, the temporal trend varied in etiologies. The ASR of mortality caused by hepatitis C virus (HCV), alcohol consumption, and non-alcoholic steatohepatitis (NASH) increased with an EAPC of 0.17 (95% CI, 0.14–0.20), 0.20 (95% CI, 0.16–0.24), 1.00 (95% CI, 0.97–1.04), respectively. A decreasing trend of ASR was found among the causes of hepatitis B virus (BV) and other causes. The increased pattern was heterogeneous worldwide. The most pronounced increase trend was found in middle-high SDI regions and Eastern Europe. Contrarily, the most pronounced decrease trend was found in low SDI regions and Western Sub-Saharan Africa. Conclusion Cirrhosis is still a public health problem. The growth trend of cirrhosis mortality caused by HCV was slowed by promoting direct-acting antiviral therapy. Unfortunately, we observed an unfavorable trend in etiologies for alcohol consumption and NASH, which indicated that more targeted and specific strategies should be established to limit alcohol consumption and promote healthy lifestyles in high-risk countries, especially in middle-high SDI regions and Eastern Europe.